A Study of Commercial Nanoparticulate γ‐Al2O3 Catalyst Supports. Issue 9 (24th April 2013) - Rozita, Yahaya; Brydson, Rik; Comyn, Tim P.; Scott, Andrew J.; Hammond, Chris; Brown, Andy; Chauruka, Sandra; Hassanpour, Ali; Young, Neil P.; Kirkland, Angus I.; Sawada, Hidetaka; Smith, Ron I.
Abstract This study investigates a range of commercially available γ‐Al2O3 powders by using a combination of integrated experimental techniques. These included general measurements of powder properties by using helium density, BET surface area, and scanning electron microscopy (SEM) analyses. In addition, dynamic light scattering and zeta potential measurements were used to investigate nanoparticle dispersions. Bulk crystal structures were analysed by using comparative X‐ray and neutron powder diffraction (XRD and NPD) analyses. Conventional transmission electron microscopy (TEM) was used to determine particle morphology, particle size, composition, and structure. Aberration‐corrected TEM was used to investigate the crystallinity of nanoparticles including the existence of any surface reconstruction on commonly observed facetted, cubeoctahedral γ‐Al2O3 nanoparticles. From the observation of peak splittings in diffraction data, we favour a description of the γ‐Al2O3 structure based on a distortion of the conventionally accepted face‐centred cubic (Fd <![CDATA[3]]> <inline-graphic xlink:href="ark:/27927/pgg36pz0q46" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />m) structure into a tetragonal I41/amd structure. Distinct differences between TEM, XRD, and NPD data indicate the presence of some cation disorder within a rigid close‐packed oxygen framework. The Rietveld refinement of the NPD data suggests a high level of microstrain of 1.2 %. An improvement to the model is achieved by reducing the aluminium content in the unit cell, which is commensurate with the migration of aluminium ions to the surface and some degree of nonstoichiometry in the particle core. Aberration‐corrected TEM imaging and exit wave reconstruction confirm previous evidence for the presence of enhanced surface contrast at 1 1 1 surface facets, which we associate with the presence of excess cation termination. In addition, these 1 1 1 facets are observed to be heavily stepped. These results may have important implications for the thermal stability of metal catalyst nanoparticles on these high‐surface area supports; the migration of aluminium ions to the surface provides clear evidence of why these materials perform so well as catalyst supports.